WATER LEVEL DETECTION FOR POTENTIAL FLOODING - Atori, Mohan Panjerino; Ghalibi, Ghazy Zahran; Nassa, Khalif Delvino Alamsyah; Akbar, M. Rizkie; Satria, Axl Banyu (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
Flooding is a situation where an area is inundated with large amounts of water. Flooding is also a natural disaster due to the negative impact of scattered rubbish. About ⅓ of The river in Cianjur overflowed due to the large amount of rubbish in the river. From these problems, we conducted useful research to analyze the potential flood conditions that could happen. Cendekia Cianjur is often hit by heavy rain and frequent flooding occurs in the area surrounding area. The research we conducted aimed to find out, anticipate and Analyze potential water conditions that can cause flooding. Of course, this is also useful for us because we can prevent flooding by measuring potential water levels. From This problem, the idea emerged to make a tool automatic function to provide warnings there will be a flood in the hope of answering unpredictable flooding problems. This system is also equipped with a prototype and can provide information on alert status and potential flooding via SMS.